2022
DOI: 10.1017/s1463423622000366
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of best practices in home enteral tube feeding

Abstract: Aims: To review the experiences of healthcare professionals (HCPs) and service users on the provision and receipt of home enteral nutrition (HEN) in primary care settings, respectively. Backgrounds: HEN supports the nutritional needs of service users in primary care settings who are unable to meet their nutritional requirements through oral intake alone. While HEN supports service users to remain in their home, the provision of HEN services can be variable. The prevalence of HEN is incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…These reports underscore the need for standardized protocols for protecting patients, monitoring medical line safety, and frequently and closely monitoring patients who have enteral tubes and use feeding sets 23,61 . A scoping review of the literature reported that most patients requiring EN can be safely and efficiently managed using standardized EN protocols 58 . To enhance the uptake and sustainability of system‐wide protocols, healthcare systems, interdisciplinary nutrition support teams, and EMR vendors can work collaboratively to build these standardized protocols into their organization‐wide policies and EMR workflows 14,58,62 …”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…These reports underscore the need for standardized protocols for protecting patients, monitoring medical line safety, and frequently and closely monitoring patients who have enteral tubes and use feeding sets 23,61 . A scoping review of the literature reported that most patients requiring EN can be safely and efficiently managed using standardized EN protocols 58 . To enhance the uptake and sustainability of system‐wide protocols, healthcare systems, interdisciplinary nutrition support teams, and EMR vendors can work collaboratively to build these standardized protocols into their organization‐wide policies and EMR workflows 14,58,62 …”
Section: Discussionmentioning
confidence: 98%
“…36 Solutions include ensuring that nurses in hospitals or patients in the home setting have current knowledge of how to use the equipment and appropriate supplies to administer EN so as to not damage the tubes or injure themselves. 58 Additionally, determining periodic automatic replenishment inventory levels and barcode scanning unit-stocked EN therapies or using standardized order sets that include ordering/delivering EN supplies for patients during the ordering process may help to improve the safety, resource use, and timeliness of care. 14,59,60 The third most common event type was patient protection events, which accounted for 14 (1%) of the reports.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations